2009
DOI: 10.1021/ja900393e
|View full text |Cite
|
Sign up to set email alerts
|

Counterion-Dependent Valence Tautomerization of Ferrocenyl-Conjugated Pyrylium Salts

Abstract: 1-Ferrocenylethynylanthraquinone (1-FcAq), which is a donor (D)-acceptor (A) conjugated compound consisting of a ferrocene (Fc) acting as a donor, an anthraquinone (Aq) acting as an acceptor, and an ethynyl linker, undergoes a cyclocondensation reaction with strong organic acid, and forms 2-ferrocenyloxodihydrodibenzochromenylium salts ([1-FcPyl](+)X(-) where X = TFSI, TfO, PF(6), and BF(4)). [1-FcPyl](+) were also characterized as conjugated donor-acceptor compounds, and electrochemical properties, UV-vis abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 60 publications
(28 reference statements)
4
29
0
Order By: Relevance
“…As was previously found for other valence‐tautomeric systems,[15b], [15e], [36b], , the distribution of the different VTs of the 2 ‐acac + radical cation is affected by its environment. As is illustrated in Figure , the positions and relative intensities of the ν(CO) bands change in different solvents.…”
Section: Resultssupporting
confidence: 68%
“…As was previously found for other valence‐tautomeric systems,[15b], [15e], [36b], , the distribution of the different VTs of the 2 ‐acac + radical cation is affected by its environment. As is illustrated in Figure , the positions and relative intensities of the ν(CO) bands change in different solvents.…”
Section: Resultssupporting
confidence: 68%
“…This taumerization, in which the cationic iron sandwich form is favored at high temperatures for the PF 6 – salt, was not observed for the BF 4 – counterpart, due to increased coulombic attraction between this smaller counter‐anion and the localized oxonium charge. This situation is somewhat reminiscent of that of α‐ferrocenylcarbonium (vide supra) . Along similar lines, this research group also reported remarkable ferrocene–dithiolene hybrids that display temperature‐gated proton‐coupled electron transfer or reversed intramolecular charge transfer in which the redox properties of ferrocene play a main role.…”
Section: The Ferrocene/ferricinium Redox Couplementioning
confidence: 73%
“…The Nishihara group discovered a counter‐anion‐dependent and thermally modulated valence tautomerization of ferrocenyl‐conjugated pyrylium salts formed by strong‐acid‐mediated cyclocondensation of 1‐(ferrocenylethynyl)anthraquinone yielding 2‐ferrocenyl‐7‐oxodihydrodibenzochromenylium salts [Equation ] …”
Section: The Ferrocene/ferricinium Redox Couplementioning
confidence: 99%
“…The IVCT band of [1,5-Am 2 Pyl 2 ] 2+ was shifted to longer wavelengths relative to [1-AmPyl] + and [1-FcPyl] + 10,11 because its pentacyclic structure possesses a more extended π-conjugated system compared with the tetracyclic compounds. The lowering of the LUMO level in [1,5-Am 2 Pyl 2 ] 2+ relative to other reported protonated compounds [10][11][12] was expected to produce more effective intramolecular charge transfer. Cyclic voltammetry of 1,5-Am 2 Aq, [1,5-Am 2 Pyl] + , and [1,5-Am 2 Pyl 2 ] 2+ in 0.1 M Bu 4 NClO 4 -CH 2 Cl 2 revealed two reversible one-electron reduction steps ascribed to the anthraquinone (Aq) and its protonated moieties (Pyl + and Pyl 2 2+ ) (Supporting Information, Figure S9).…”
Section: Protonation Of 15-am 2 Aq and Properties Of The Productsmentioning
confidence: 89%
“…Because the electronic structure of a molecule directly influences its physical properties, 5-7 the electronic properties can be employed to achieve switching behavior in molecular devices. 8,9 We have previously described a new class of D-A molecules comprising a 1:1 donor/acceptor formula, 1-RAq, [10][11][12] in which R () ferrrocenyl (Fc), phenyl, m-tolyl, or p-tolyl) and Aq (anthraquinone) undergo intramolecular cyclization to give pyrylium cations [1-RPyl] + . This phenomenon can be used to lower the energy of the lowest unoccupied molecular orbital Inorg.…”
Section: Introductionmentioning
confidence: 99%